Best Practices in the Diagnosis and Treatment of Atrial Fibrillation. Issue 28 (29th October 2015) - Cunningham, Muriel
Treatment of patients with atrial fibrillation should be customized for each individual. Embolic and bleeding risk should be assessed when anticoagulating these patients to determine the optimal therapeutic approach. Recent evidence has shown that lifestyle modifications such as weight loss and exercise can benefit patients with atrial fibrillation.